Ocular melanoma: keep your eyes open for late brain metastases - Silva, Danilo Otávio de Araújo (2011)
Background:The most frequent intraocular malignant tumor is choroidal melanoma (CM). Although brain metastasis is a common feature of other types of cancers, metastasis of CM to the brain is a rare entity. Case Description:The authors report a case of a 28-year-old woman presenting with a single brain metastasis, 10 years after the treatment of a CM. She underwent a total en-bloc resection of the lesion, and the diagnosis was conﬁrmed histopathologically. The patient concomitantly received whole-brain irradiation therapy combined with chemotherapy, with a survival period of 24 months. Conclusion:The present case report draws attention to the necessity of a close and lifelong follow-up of patients treated for this malignancy. The international literature is also reviewed.